2015
DOI: 10.1007/s11999-014-4068-x
|View full text |Cite
|
Sign up to set email alerts
|

Twelve Percent of Hips With a Primary Cam Deformity Exhibit a Slip-like Morphology Resembling Sequelae of Slipped Capital Femoral Epiphysis

Abstract: Background In some hips with cam-type femoroacetabular impingement (FAI), we observed a morphology resembling a more subtle form of slipped capital femoral epiphysis (SCFE). Theoretically, the morphology in these hips should differ from hips with a primary cam-type deformity. Questions/purposes We asked if (1) head-neck offset; (2) epiphyseal angle; and (3) tilt angle differ among hips with a slip-like morphology, idiopathic cam, hips after in situ pinning of SCFE, and normal hips; and (4) what is the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 28 publications
(66 reference statements)
1
36
0
3
Order By: Relevance
“…Exclusion criteria were: A history of hip pathology or symptoms; genetic, neuromuscular or developmental condition; and low‐quality CT images precluding 3D reformatting. A total of 80 subjects (age: 8–15 years; 10 per age group; 50% females) with normal hips were selected, Hip normality was verified radiographically by measuring alpha angle, epiphyseal tilt angle, and the acetabular index angle . Details of patients selection process and their baseline characteristics are previously reported in a study focused on age‐ and sex‐related changes in development of capital femoral epiphysis morphology .…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria were: A history of hip pathology or symptoms; genetic, neuromuscular or developmental condition; and low‐quality CT images precluding 3D reformatting. A total of 80 subjects (age: 8–15 years; 10 per age group; 50% females) with normal hips were selected, Hip normality was verified radiographically by measuring alpha angle, epiphyseal tilt angle, and the acetabular index angle . Details of patients selection process and their baseline characteristics are previously reported in a study focused on age‐ and sex‐related changes in development of capital femoral epiphysis morphology .…”
Section: Methodsmentioning
confidence: 99%
“…Subclinical slipped capital femoral epiphysis (SCFE) has been proposed as the possible pathomechanism of cam‐type FAI. In a cohort of 200 patients with cam impingement, Albers et al have shown that a post‐slip morphology was present in only 12%. The highest prevalence (72%) in the cohort contained hips with idiopathic cam‐type morphology with a normal epiphyseal angle but increased epiphyseal extension.…”
Section: Development Of Cam‐type Faimentioning
confidence: 99%
“…The presence of such deformities may predispose one to FAI. However, FAI is a dynamic process, which can only be diagnosed clinically and differs from the idiopathic cam deformity (83). Two imaging signs are helpful to detect the slip-like morphology: the fovea sign and the tilt angle (83), both seen on radial MR images at the 2 o'clock anterosuperior position.…”
Section: Extraarticular Hip Impingementmentioning
confidence: 99%
“…The fovea sign is positive if the femoral neck axis does not cross the fovea capitis femoris. The tilt angle is calculated between the femoral neck axis and the line perpendicular to the connecting line between the two ends of the femoral epiphysis and is positive if the angle is greater than 4° (83). These signs may be more useful in research than in the clinical routine, as therapy is not different between idiopathic and slip-like cam deformities.…”
Section: Extraarticular Hip Impingementmentioning
confidence: 99%